The Application of Audiovisual-Based Learning Media to Increase Students' Learning Interest in The Material of Ratios and Diagrams in Grade 5 SD Negeri 101943 Bengkel - Fadli, Khairu; Hasanah, Hasanah; Siregar, Nurhafni; Hiras, Hiras; Hermawan, Hermawan (Education Achievement: Journal of Science and Research, 2024)
There is a gap in interest with one of the subjects that students do not like. The aim of this research is to grow and increase students' interest in learning, especially in learning mathematics using audio-visual media on student learning outcomes in ratio and diagram material. The subjects of this research were the VB SD class with a total of 19 students. The time for carrying out the PTK research in the form of applying audiovisual media to mathematics subjects regarding ratios was carried out from May 2024 to June 2024. The research instruments used in this PTK were question sheets, observation sheets and documentation. Meanwhile, data collection techniques include observation and documentation. Based on student learning outcomes, it was obtained at 42.1% and for student interest in learning, it was obtained at 26.31% in the pre-cycle carried out. The results obtained from cycle 1 were that student learning outcomes were 57.89% and student interest in learning was 47.36%. Based on the results obtained from cycle 2 activities, namely student learning outcomes and student interest in learning were at 73.68%, this shows that the media is proven and successful in increasing students' learning interest in ratio and diagram material.